Dietary inclusion of African bush mango (Irvingia gabonensis) seed improves sexual performance in sexually inexperienced rats - Olasunkanmi Omojokun; Akindele Famurewa; Ganiyu Oboh; Jemima Enang; Stella Ijeh (Academia Biology)
Background: Erectile dysfunction (ED) is a sexual dysfunction characterized by the persistent inability to develop or maintain an erection of penis sufficient for satisfactory sexual relation. Synthetic aphrodisiacs have reportedly been used for the management of ED, but they present with some side effects. This research sought to evaluate the enhancing potential of diet-supplemented African bush mango (ABM) seed on erectile function in sexually inexperienced rats. Results: For this study, weaned male (28) and female (28) rats were procured. Rats were separately nurtured to maturity and grouped into four of seven rats in a group (n = 7). Group 1 received basal diet, Group 2 received basal diet with sildenafil (5 mg/kg body weight), Group 3 were fed diet with 10% ABM seed inclusion, while Group 4 were fed diet with 20% ABM seed inclusion. The experiment lasted for 21 days after which behavioral studies involving sexual and anxiety indices/measurements, lipid peroxidation, and enzyme assays (arginase and phosphodiesterase-5 [PDE-5]) were conducted. The group with diet inclusion containing 20% ABM showed an obviously increased sexual behavior similar to the group that received sildenafil. Arginase and PDE-5 inhibitory activities were also higher in the same group. Conclusion: This study suggests that ABM promotes sexual behavior and improves penile erection as a treatment for ED, justifying its use in folk medicine for this purpose.